3(4n+2)=-2(4n+6)

Simple and best practice solution for 3(4n+2)=-2(4n+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4n+2)=-2(4n+6) equation:



3(4n+2)=-2(4n+6)
We move all terms to the left:
3(4n+2)-(-2(4n+6))=0
We multiply parentheses
12n-(-2(4n+6))+6=0
We calculate terms in parentheses: -(-2(4n+6)), so:
-2(4n+6)
We multiply parentheses
-8n-12
Back to the equation:
-(-8n-12)
We get rid of parentheses
12n+8n+12+6=0
We add all the numbers together, and all the variables
20n+18=0
We move all terms containing n to the left, all other terms to the right
20n=-18
n=-18/20
n=-9/10

See similar equations:

| -9x+30=-5(x+2) | | (8x+9)=(11x+12) | | 2(6x-3)=7(7x-1.2) | | 115+(x+27)=180 | | (4v-3)(v-5=) | | –8s+7=–7s | | 26=6k | | 7(x+5)=24 | | |5m+9|=-31 | | -4r+8+5=-15-3r | | 5w+8.6=-3.4 | | 8(x+5.75)=16(3x+1.50) | | 3/5(x-19)=5 | | 9-2(x+7)=21 | | 22+54x=+60x | | 120=6r | | 5y+6=4y+12 | | 16.95+(.5n)=22.95+(.2n) | | 24m-12=-84 | | 70=3g | | u-2.89=9.3 | | 90=6x-2+20 | | 24=12a-6 | | (5x+10)=(7x+6) | | 4=n+15/9 | | -7+3x=-1x+17 | | y=1/4–2 | | 9(x-2)=830 | | -(15x+3)=-3x-9 | | 19x=1,995 | | y2–45y=0 | | 76+67+5x+2=180 |

Equations solver categories